THE IMPACT OF OVERCONFIDENCE AND TRAIT ANXIETY ON INVESTMENT DECISIONS AMONG GENERATION Z - Vera Handayana Wibowo; Agus Zainul Arifin (International Journal of Application on Economics and Business, 2025)
Investment decisions are not only influenced by rational considerations but also by psychological factors, such as overconfidence and trait anxiety. This study aims to describe the impact of these two psychological characteristics on the investment decisions of Generation Z individuals living in the JABODETABEK area. A descriptive quantitative approach was applied, and data were collected through an online survey involving 200 respondents with prior or current investment experience. The data were analyzed using Structural Equation Modeling (SEM) to examine the relationships between psychological traits and investment behavior. The findings reveal that overconfidence has a positive and significant influence on investment decisions. Generation Z investors tend to overestimate their own knowledge and forecasting abilities, making them more prone to taking high-risk investment decisions. These results are in line with Prospect Theory, which emphasizes the dominant role of cognitive biases, especially overconfidence, in financial decision-making under conditions of uncertainty. In contrast, trait anxiety does not appear to significantly influence investment behavior, although anxiety is theoretically known to affect risk perception and decision-making processes. Based on these findings, the study recommends the inclusion of financial literacy as an additional variable in future research, as it may serve as a mitigating factor to reduce the negative effects of overconfidence and promote more rational investment decisions, particularly among young and less experienced investors.